Plant Recycling for Molecular Biofarming to Produce Recombinant Anti-Cancer mAb - Kim, Deuk-Su; Song, Ilchan; Kim, Jinhee; Kim, Do-Sun; Ko, Kisung (Frontiers in Plant Science, 2016)
The expression and glycosylation patterns of anti-colorectal cancer therapeutic monoclonal antibody (mAb) CO17-1A recognizing the tumor-associated antigen GA733-2, expressed in human colorectal carcinoma cells, were observed in the leaf and stem tissues of primary (T2; 0 cycle) secondary (1 cycle), and tertiary (2 cycle) growths of seedlings obtained from the stem cut of T2 plants. The bottom portion of the stem of T2 seedlings was cut to induce the 1 cycle shoot growth, which was again cut to induce the 2 cycle shoot growth. In the 1 and 2 cycle growths, the periods for floral organ formation was shorter (35 days) than that (100 days) for the 0 cycle growth. The genes of heavy and light chains of mAb CO17-1A existed at the top, middle, and basal portions of the leaves and stem obtained from the 0, 1, and 2 cycle plants. The protein levels in the leaves and stem tissues from the 1 and 2 cycles were similar to those in the tissues from the 0 cycle. The glycosylation level and pattern in the leaf and stem did not alter dramatically over the different cycles. Surface plasmon resonance (SPR) confirmed that mAbs CO17-1A obtained from leaf and stem tissues of the 0, 1, and 2 cycles had similar binding affinity for the GA733-2 antigen. These data suggest that the shoot growth by bottom stem cutting is applicable to speed up the growth of plant biomass expressing anti-colorectal cancer mAb without variation of expression, glycosylation, and functionality.